Investigating the role of CD47 gene regulation in Iraqi cancer patients: a promising prognostic factor: CD47 Regulation in Iraqi Cancers - Jabbar, Shilan; Ismael, Athraa (Iraqi Journal of Cancer and Medical Genetics, 2023)
Background: Innate immune checkpoints have been one of the most studied and promising approaches in cancer immune therapy. Therefore, it is considered valuable when investigating these checkpoints at the gene expression and protein levels. However, this approach still has variations from study to study due to various types of cancer. Therefore, it is hypothesized that CD47 could be one of those checkpoints that affect the survival of cancer cells. CD47 is an integrin like marker that has been identified for its role as “do not eat me signal” which enhances the ability of cancer cells to escape from being phagocytized by macrophages. Aim of the study: This study aims to investigate CD47 expression in ten solid tumors and five blood cancers at the gene level and at the protein level. Methods: Clinical specimens were collected from patients with different cancers attending Kirkuk oncology center. The patients were categorized into two main groups: solid tumor group and blood-derived cancer group together with their control counterparts. CD47 gene expression was investigated using q RT-PCR techniques while its protein levels were investigated using ELISA techniques. Results: The results showed a significant up-regulation of CD47 gene expression in gastric cancer, cholangiocarcinoma; CCA (bile duct), chronic myeloid leukemia (CML), and breast cancer, respectively. These results were also confirmed at the protein level, suggesting that those types of malignancy are more susceptible to an increase in CD47 expression than other types of cancer that were involved in this study. Conclusion: CD47 tends to be over-expressed in solid tumors and blood cancers, and could be used as diagnostic and prognostic markers, especially for solid tumors.